Photophysical processes of an intramolecular charge transfer fluorescent dye with carbazole units. (3rd July 2012) - Gao, Shouqin; Hao, Liling; Li, Junfen; Lin, Peihua; Li, Duxin; Shuang, Shaomin; Dong, Chuan
ABSTRACT: A carbazole‐based compound with intramolecular charge transfer (ICT) characteristics, 3, 6‐bis‐((N‐ethylcarbazole‐3‐)‐propene‐1‐keto)‐N‐ethylcarbazole (BCzPCz) was synthesized by N‐alkylation, acetylation and aldol condensation. BCzPCz was further confirmed by IR and 1  H NMR. The central N‐ethylcarbazole was connected with two N‐ethylcarbazole units through the propenone group in BCzPCz. N‐ethylcarbazole and carbonyl groups were electron donors (D) and acceptors (A), respectively. The UV–vis absorption and fluorescence characteristics of BCzPCz were also investigated in different solvents. Solvatochromism was attributed to ICT complex formation in singlet excited state. Magnitude of the change in the dipole moment was 24.78 D according to Lippert‐Mataga equation. Fluorescence of BCzPCz was significantly affected by pH and was quenched in acidic medium. Fluorescence quantum yield of BCzPCz was 0.516 in ethanol. Experimental results showed its potential use as a fluorescence probe and as two‐photon absorption material. Copyright © 2012 John Wiley & Sons, Ltd.